2022
DOI: 10.1002/smll.202200046
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Solvation Chemistry for the Solution of High‐Donor‐Number Solvent for Stable Li–S Batteries

Abstract: Passivation of the sulfur electrode by insulating lithium sulfide (Li2S) restricts the reversibility and sulfur utilization of lithium–sulfur (Li–S) batteries. Although electrolytes with high donor number (DN) solvents induce tri‐sulfur radical intermediate thus 3D nucleation of Li2S with fast kinetics can be achieved, their catastrophic reactivities with Li metal hinder practical applications. Here, the use of high DN solvent as an additive instead of as co‐solvent to solve their incompatibility between catho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 64 publications
3
33
0
Order By: Relevance
“…To better understand the interaction mechanism between PC and graphite, particularly in electrolytes that support reversible Li-intercalation into graphite when a large proportion of PC is present, we selected N -methylpyrrolidone (NMP, DN = 27.3) as another high-donicity cosolvent to pair with PC. NMP, a massively devoured industrial solvent for the electrode manufacturing of Li-ion batteries, is seldomly considered as a solvent in the electrolyte. , Indeed, in this study, we demonstrated that it was incompatible with the graphite anode, by displaying an analogously irreversible cointercalation process to PC. However, an intriguing synergy was discovered when NMP was united with PC: solvent cointercalation disappeared and Li + could be reversibly intercalated into graphite.…”
Section: Introductionmentioning
confidence: 68%
“…To better understand the interaction mechanism between PC and graphite, particularly in electrolytes that support reversible Li-intercalation into graphite when a large proportion of PC is present, we selected N -methylpyrrolidone (NMP, DN = 27.3) as another high-donicity cosolvent to pair with PC. NMP, a massively devoured industrial solvent for the electrode manufacturing of Li-ion batteries, is seldomly considered as a solvent in the electrolyte. , Indeed, in this study, we demonstrated that it was incompatible with the graphite anode, by displaying an analogously irreversible cointercalation process to PC. However, an intriguing synergy was discovered when NMP was united with PC: solvent cointercalation disappeared and Li + could be reversibly intercalated into graphite.…”
Section: Introductionmentioning
confidence: 68%
“…Solvents with high polarity (e.g., ACN, dimethylformamide, and dimethyl sulfoxide) induce a dissociation equilibrium in which S 3 •– radical anions are the dominant chemical species . The S 3 •– radical anions are stabilized in highly polar solvents because the Li + –S 2– interaction weakens by competing electrostatic interactions from the solvent. , Taking this into consideration, the presence of EtOH enhances the chemical stability of the polysulfides, particularly, the S 3 •– radical anions, owing to the strong interaction between Li + and EtOH. This is also observed from the UV–vis spectra of 5Li 2 S·P 2 S 5 ·2LiX·15S (X = Br and I) in the THF/ACN/EtOH solvent, as shown in Figure b,c.…”
Section: Resultsmentioning
confidence: 99%
“…•− radical anions are stabilized in highly polar solvents because the Li + −S 2− interaction weakens by competing electrostatic interactions from the solvent. 26,27 Taking this into consideration, the presence of EtOH enhances the chemical stability of the polysulfides, particularly, the S 3…”
Section: Solubility Of 5li 2 S•p 2 S 5 •2licl•xs Solutionmentioning
confidence: 99%
“…Rechargeable Li–S batteries have been regarded as one of the most promising candidates for next-generation energy storage systems because of their amazing energy density (2600 Wh kg –1 ), high capacity (1675 mAh g –1 ), and abundant sulfur reserves. However, the commercialization of Li–S batteries is seriously plagued by the “shuttle effect” and sluggish reaction kinetics. The dissolution of higher-order polysulfides into solvents [lithium polysulfide (LiPS) shuttle] gives rise to severe self-discharge and a low Coulombic efficiency. Furthermore, the slow redox kinetics hinders rapid charging, leads to accumulation of the LiPSs in the solvent, and aggravates the shuttle effect at the same time.…”
mentioning
confidence: 99%